Overview of Related Features of Viral Hepatitis: From Pathogenesis to Prevention, Treatment, and Complications - Ronald P. Cabral M.D; Rachelle C. Gutierrez MLT (PT FORMOSA CENDEKIA GLOBAL, 2023)
EnglishViral hepatitis is a significant global health issue with multiple aspects that require attention. This article will provide an overview of the discussions on viral hepatitis, including pathogenesis, serologic markers, prevention and treatment strategies, and complications or sequelae associated with hepatitis A, B, C, D, and E. The pathogenesis section explores the distinct mechanisms of viral entry, replication, and immune response for each hepatitis virus, highlighting the importance of understanding these processes for targeted therapies and preventive measures. Serologic markers play a crucial role in the diagnosis of viral hepatitis, and their detection enables accurate diagnosis, differentiation of acute and chronic infections, and assessment of disease progression and treatment response. Prevention strategies, such as vaccination, safe injection practices, blood and organ screening, and safe sex practices, are essential for reducing the transmission and burden of viral hepatitis. Treatment strategies, including antiviral therapy and supportive care, are discussed for the management of chronic hepatitis and associated complications.